Six Sigma deployment at Tata Communications Limited, India : a case study - Anantharaman, Senthil Kumar; Kapoor, Rohit (London : NeilsonJournals Publishing, 2018)
Tata Communications Limited, a leading global telecom giant headquartered in Mumbai, India was facing a grave situation of losing clients in its unified communication services. The situation arose due to high delivery turnaround times in order processing which were mainly due to redundant process steps and sales operations. This case provides, a step-by-step analysis in continuous improvement and deploying Six Sigma systematically. Students apply the structured Six Sigma based Define, Measure, Analyse, Improve and Control (DMAIC) methodology to improve the process. They define the problem, collect appropriate measures, calculate sigma levels using process capability analyses and arrive at root causes using fishbone and affinity diagrams. Students also brainstorm common sense solutions to address and prioritise the root causes using appropriate tools such as prioritisation matrix. Finally, students suggest suitable plans to control and sustain the solutions. Our case helps students to understand the basics of Six Sigma in solving complex problems faced in a telecom-oriented service industry thereby providing them with experience of real-world industry problems.
Originally Published In Anantharaman, S., & Kapoor, R. (2018). Six Sigma Deployment at Tata Communications Limited, India - A Case Study. Operations Management Education Review, 12(1), 101-122. OMER12-0CS4.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Telecommunication -- India -- Mumbai -- Case studies; Telecommunication -- Decision making -- Case studies